Estimating biological capacity for grass-finished ruminant meat production in New England and New York. (April 2021) - Thorn, Alexandra M.; Baker, Michael J.; Peters, Christian J.
ABSTRACT: The Northeastern United States contributes a small share to national meat production. However, increasing interest in local food production and on-going challenges posed by drought and fire on Western rangelands give reason to believe that the importance of Northeastern grass-based ruminant meat could grow in the near future. Using an integrated modeling approach, the present study quantifies current and potential biological capacity for grass-based ruminant meat production in New York and New England. We used the Cropland Data Layer (CDL) to establish the area and spatial distribution of hay and pasture, with area estimates validated against the USDA Census of Agriculture. Potential forage productivity was modeled using ordinary least squares linear regression of SSURGO non-irrigated crop yield values for pasture against NICC classes and subclasses, drainage classes, slope, air temperature, and quintiles of depth to restrictive soil layers, using ordinary least squares linear regression. Forage yield gaps were calculated by comparing potential productivity to annual crop survey data from the USDA. The potential production of grass-finished cattle based on either current or potential forage yields based on models of feed needs for spring- and fall-calving herds produced using the Large Ruminant Nutritional System. We show that more than half of agricultural land cover currently appears to be pasture, but that only some of this land is actively used for grazing, with actual yields just 54% or 47% of economic yields for hay and pasture respectively. Overall, we estimate the potential to increase the regional beef herd size by 90% to 270% by increasing yields, expanding production into unutilized grassland area, or both. We conclude that up to 3% of U.S. beef could be produced in the region, on less than 0.5% of U.S. agricultural land area, pointing to high potential for sustainable intensification of beef production in the Northeastern United States. Realizing this potential, however, requires closing of yield gaps and intensification of the use of land in agricultural cover. The amount of biophysical productivity that is economically attainable remains highly uncertain.